A modern tradition: the social history of the Zimbabwean Marimba - Jones, Claire (International Library of African Music, 2012)
Zimbabwean pop superstar Oliver Mtukudzi surprised his fans with a new lineup in 2007, replacing his trademark keyboard and electric guitar with marimba and mbira. 'Tuku' declared: "This change will inspire the younger generation of artists and make them proud of our traditional instruments” (Mtukudzi n. d). But the Zimbabwean marimba, widespread in urban schools and tourist venues, dates only from the early 1960s, when African xylophones of a modern design were introduced at the Kwanongoma College ofAfrican Music in Bulawayo. The white Rhodesian founders of the private college considered the marimba, then unassociated with the musical practices of the country's major ethnicgroups, an ideal instrument to "serve as a focal point for musical development of the new nation” (Tracey pers. comm. 1989). Today the Kwanongoma marimba is considered by many Zimbabweans to be "part of our culture.”
Keywords: Marimba; African Music; Zimbabwe; Social History; Marimba (Instrument)